Model Pelestarian Lingkungan Hidup Berbasis Teknologi Informasi pada Aktivitas Sosialisasi Berbasis Masyarakat Sebagai Sentra Partisipan - Wahyu Sardjono (Bina Nusantara University, 2011)
The environment is a gift and grace of the Almighty God to man as home to life. In utilizing natural resources to promote human welfare, a sustainable environmental development should be carried out, which cares about the needs of present and future generations. On the other hand, the development of information and communication technology (ICT) grows so fast that can change the way people live and work. Collaboration between the environment and its preservation with ICT knowledge can be developed into an environmental knowledge and management system (E-KMS). An approach to efficiency and effectiveness in ICT which includes variables of timing, capacity, relevance, accessibility, flexibility, accuracy and reliability can be used to explore the determinants of the success of the socialization of community-based environmental conservation as a central participant. The multivariate statistical methods and factor analysis can produce new variables declared as an indicator of research results and model testing.